MENULIS PUISI BARU DENGAN MENGGUNAKAN METODE PEMBELAJARAN PROJECT BASED LEARNING DI TINGKAT SEKOLAH MENENGAH ATAS - Siti Mariah; Mauliyah Ummah; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The main problem in this research is the low ability of students to write poetry in class X. To overcome the problem is offered one of the learning method that is project based learning method. The purpose of this research is to know the implementation of learning to write poetry by using project based learning method in class X to know the result of the students about learning to write poetry before and after being treated by using project based learning method. Research conducted in the field using experimental research methods. The data processing using SPSS. The instruments prepared are the observation and test sheets. The results of this study indicate that the implementation of learning to write poetry in class X by using project based learning method is in accordance with the stages of learning planned. The result of learning to write poetry using project based learning method looks good because it can be seen from the average initial test score is 47.2 and final test 61,4 so that there is 36% improvement from initial test to final test. This means that learning poetry writing is effectively applied by using problem based learning method.